Diagnostik und konservative Therapie zervikaler und lumbaler Spinalkanalstenosen - Hug, Andreas; Hähnel, Stefan; Weidner, Norbert (Der Nervenarzt, 2018)
BackgroundDegenerative stenotic spondylosis is not an uncommon cause of cervical spondylotic myelopathy (CSM) and cauda equina lesions in the aged population. Limited standardization exists with respect to diagnostic and therapeutic procedures.ObjectiveLiterature review with respect to diagnostic and therapeutic procedures for neurologically relevant cervical and lumbar spinals stenosis.Material and methodsComprehensive literature review.Results and conclusionClinical neurological examination and diagnostic imaging are fundamental for the diagnosis of neurologically relevant cervical and lumbar spinal stenosis. Additional laboratory blood and cerebrospinal fluid testing might be required for a differential diagnosis. Neurophysiological testing is reserved for specific clinical problems. The clinical evidence for the efficacy of conservative therapeutic strategies is limited.
Gesehen am 18.11.2019